The application of Lu-Al-Si-O-N oxynitride glass in transparent AlON ceramics joining. Issue 2 (1st February 2019) - Liang, Hanqin; Guo, Huilu; Yin, Jinwei; Zuo, Kaihui; Xia, Yongfeng; Yao, Dongxu; Zhang, Jian; Zeng, Yuping; Wang, Shiwei
Abstract: Transparent AlON ceramics were bonded with Lu-Al-Si-O-N oxynitride glass interlayer at 1450 °C in nitrogen atmosphere in this investigation. The Lu-Al-Si-O-N oxynitride glass showed good wettability on the AlON substrate and had strong interface adhesion with each other. The joining process had no detrimental effect on the in-line transmittance of transparent AlON ceramics but caused slight decrease of flexural strength due to the partial decomposition. The bonding strength of AlON/AlON joint was 142.7 ± 6.3 MPa at room temperature and 110.1 ± 9.6 MPa at 1200 °C in situ, which were comparable with those of the parent AlON ceramics. Some Lu2 Si2 O7 grains crystallized out from the glass interlayer after joining.